Fostering Tolerance Through Religious Moderation in Teaching and Learning at SDN 1 Bakalrejo - Yaqin, Ahmad Nurul; Junaidi, Mahbub; Umroh, Ida Latifatul (Universitas Islam Sultan Agung, 2025)
This research uses a descriptive qualitative design to explore the implementation of religious moderation values in teaching and learning activities, and their impact on students’ attitudes of tolerance at SD Negeri 1 Bakalrejo. Although all students are Muslim, internal diversity exists due to different religious orientations such as Nahdlatul Ulama, Muhammadiyah, and Salafi. This diversity may lead to potential conflict if not properly managed. Data were collected through observation, interviews, and documentation. Participants included classroom teachers, Islamic education teachers, the principal, students in grades IV to VI, and selected parents using purposive sampling. The findings reveal that religious moderation values are integrated into both formal and non-formal learning. Teachers act as facilitators using open discussions, simple analogies, and practical applications of diversity values. This strategy leads to increased mutual respect, reduced blaming behaviors, and greater curiosity among students regarding religious differences. Parents also observed positive changes in their children, who became more open and inclusive. The program's success is supported by the principal's commitment, teacher awareness, and parental involvement. These findings emphasize the importance of religious moderation in primary education to shape a tolerant, peaceful, and religiously grounded generation.